Tinjauan Yuridis Terhadap Ganti Rugi Tanah Untuk Pembangunan Kepentingan Umum Antara Pemilik Tanah Dengan Pemerintah Kabupaten Rote Ndao : Studi Putusan Nomor 46/Pdt.G/2021/Pn Rno - Risal Ariyanto Lilo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Land acquisition is an activity to provide land by providing adequate and fair compensation to the entitled party, either in the form of money, replacement land, resettlement, share ownership, or other forms agreed by both parties. The issue of compensation is one of the disputes that must be resolved in court and takes quite a long time. This study aims to determine how the judge's considerations are in decision Number 46 / Pdt.G / 2021 / Pn Rno and to find out the legal consequences for both parties in decision Number 46 / Pdt.G / 2021 / Pn Rno. This research is a normative legal research. Normative legal research, or legal research, is generally based on document studies by relying on legal sources such as laws and regulations, court decisions, legal theories, and expert opinions. The object of research in this writing focuses on a case study of a court decision with case number 46 / Pdt.G / 2021 / Pn Rno. The results of the study indicate that the unlawful act case filed at the Rote Ndao District Court has been implemented. The case has been decided fairly by the judge without harming either party/ so that the defendant, as the losing party, is obliged to pay compensation to the plaintiff and in return the plaintiff surrenders his land to be used as a regional government asset in the context of public services for the Rote Ndao community. Based on this, both parties should coordinate and involve related parties to find a bright spot. The government is also expected to be able to socialize the compensation case to the community. This is useful to prevent legal problems from arising in the future.